Synthesis and Antimicrobial Activity of 4-aryl furo Pyridazines - Singh, Ashok Kumar; Srivastav, Narendra Kumar (Journal of Nepal Chemical Society, 2013)
Benzoyl hydrazides (1a-b) was condensed with furan-2-aldehyde (2) in the presence of sodium hydroxide and dry ethanol, furan-2-yl-benzoyl hydrazone (3a-b) was achieved. Intramolecular cyclization of compound 3a-b with PPE afforded 4-aryl furo pyridazines (4a-b)DOI: http://dx.doi.org/10.3126/jncs.v30i0.9338Journal of Nepal Chemical Society Vol. 30, 2012 Page:  66-70 Uploaded date: 12/16/2013